Effects of Optaflexx™ on finishing steer performance and USDA quality and yield grades - E.R. Loe; T.J. Klopfenstein; G.E. Erickson; B.E. Dicke; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2005)
Crossbred yearling steers (2,015 head) were fed at a commercial feedyard near Larned, Kansas, to evaluate the effects of feeding Optaflexx™ at 0 or 200 mg ractopamine-HCl per steer daily for the final 29 days on feed. Steers were fed a common diet, based on steam-flaked corn, throughout their finishing period. Cattle that were fed Optaflexx™ had heavier final bodyweights (1264 vs. 1236 lb). Optaflexx™-fed cattle gained 17.9% faster (carcass adjusted basis) and tended to consume more feed during the last 29 days on feed. Feed efficiency was 14% better during the last 29 days for the Optaflexx™-fed steers. Feeding Optaflexx™ increased carcass weight by 19.7 lb and increased carcass weight gained during the last 29 days on feed by 11.2 lb. There were more liver abscesses for the control steers (19.7%) than for Optaflexx™-fed steers (13.5%). Quality grade was not affected by feeding Optaflexx™. There was a decrease in USDA Yield Grade 2 carcasses (49.6 vs. 54.8%) and an increase in USDA Yield Grade 4 carcasses (3.3 vs 1.7%) when cattle were fed Optaflexx™. Performance of the steers from the time that they were sorted into their treatment pens until slaughter (98 days) was improved by feeding Optaflexx™ during the last 29 days on feed. For the full 98-day period, daily gain was 8% greater for steers fed Optaflexx™ vs. control, feed intake was greater for the steers fed Optaflexx™, and feed efficiency was moderately improved (3.3%). Steers that received Optaflexx™ gained 6.4% more bodyweight during the 98-day feeding period. These data show that addition of Optaflexx™ into finishing diets fed to steers is beneficial, increasing bodyweight and carcass gain and improving conversion of feed to beef without affecting USDA quality grade.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Optaflexx; Steer performance; USDA quality grades; USDA yield grades